2022
DOI: 10.1128/spectrum.01053-21
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome-Targeted Modulations Regulate Metabolic Profiles and Alleviate Altitude-Related Cardiac Hypertrophy in Rats

Abstract: Evidence suggests that gut microbiome changes upon hypobaric hypoxia exposure; however, it remains elusive whether this microbiome change is a merely derivational reflection of host physiological alteration, or it synergizes to exacerbate high-altitude diseases. We intervened gut microbiome in the rat model of prolonged hypobaric hypoxia challenge and found that the intervention could alleviate the symptoms of pathological cardiac hypertrophy, gut microbial dysbiosis, and metabolic disruptions of certain metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…In addition, acute hypoxia exposure leads to changes in intestinal barrier permeability 22 and gut microbiota composition 23 , resulting in host maladaption to high altitude and incidence of AMS 24 . Increased Parabacteroides , Akkermansia , Lactobacillus , Bacteroides , and decreased Prevotella were also found in human and animal models of AHH exposure 25 28 . Bacteroides , Parabacteroides , Butyricimonas , Lactobacillus , Phascolarctobacterium , and Akkermansia are intestinal commensal bacteria, most of whom are SCFAs producing bacteria 28 30 .…”
Section: Discussionmentioning
confidence: 89%
“…In addition, acute hypoxia exposure leads to changes in intestinal barrier permeability 22 and gut microbiota composition 23 , resulting in host maladaption to high altitude and incidence of AMS 24 . Increased Parabacteroides , Akkermansia , Lactobacillus , Bacteroides , and decreased Prevotella were also found in human and animal models of AHH exposure 25 28 . Bacteroides , Parabacteroides , Butyricimonas , Lactobacillus , Phascolarctobacterium , and Akkermansia are intestinal commensal bacteria, most of whom are SCFAs producing bacteria 28 30 .…”
Section: Discussionmentioning
confidence: 89%
“…Specifically, Lactobacillaceae probiotics possess antitumor, antitoxic, cholesterol-lowering, antibacterial, and antiviral activity ( Nazir et al, 2018 ). Hu et al (2022) found that the abundance of Lactobacillaceae changed with prolonged hypoxic exposure in a hypoxic environment. Based on the above studies, we believe that changes in the abundance of Lactobacilli may be a defining feature after hypobaric hypoxia exposure, which is of great significance for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, plateau pikas and plateau pikas are rich in members of the families Lachnospiraceae and Clostridiaceae, which not only may enhance energy acquisition from food but also convert dietary fibers into SCFA ( Wang et al, 2022 ). SCFAs primarily suppress inflammation by inhibiting the NF-κB pathway and/or histone deacetylase (HDAC) functionality, thereby downregulating pro-inflammatory cytokines ( Hu et al, 2022 ). Similar phenomena have been observed in other high-altitude species.…”
Section: Impact Of Intestinal Microbiota Alterations On Organismal He...mentioning
confidence: 99%
“…The adverse conditions present in high-altitude environments have driven natural selection among populations ( Bai et al, 2022 ). Factors such as hypobaric hypoxia, low temperatures, and high radiation not only impact organismal reproduction and survival but also accelerate population-level evolution and physiological adaptations ( Hu et al, 2022 ). These conditions may also precipitate high-altitude reactions or illnesses in susceptible individuals, potentially leading to dysbiosis in the intestinal microbiota ( Lan et al, 2017 ; Zuo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%